2023
DOI: 10.1364/oe.488353
|View full text |Cite
|
Sign up to set email alerts
|

Sub-kHz high-order mode Brillouin random fiber laser based on long-period fiber grating and distributed Rayleigh scattering in a half-open linear cavity

Abstract: We demonstrate a narrow-linewidth high-order-mode (HOM) Brillouin random fiber laser (BRFL) based on a long-period fiber grating (LPFG) and distributed Rayleigh random feedback in a half-open linear cavity. The single-mode operation of the laser radiation with sub-kilohertz linewidth is achieved thanks to distributed Brillouin amplification and Rayleigh scattering along kilometer-long single mode fibers whilst a few mode fiber-based LPFGs enable the transverse mode conversion among a broadband wavelength range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Very recently, a narrow-linewidth high-order-mode BRFL was presented with the help of an LPFG, which is inscribed in FMF, SBS gain, and Rayleigh backscattering feedback. [177] As can be seen in Figure 10b, the 3 dB linewidth of the high-order-mode Brillouin random fiber lasing (the red curve in the inset) is as narrow as 230 Hz, even with the pump linewidth of 15.2 kHz (the purple curve in Figure 10b). In such a BRFL, the FMF-based LPFG enables the transverse mode conversion among a broad wavelength range.…”
Section: Narrow-linewidth Rfls Based On Sbs Gain or Pmfmentioning
confidence: 91%
See 2 more Smart Citations
“…Very recently, a narrow-linewidth high-order-mode BRFL was presented with the help of an LPFG, which is inscribed in FMF, SBS gain, and Rayleigh backscattering feedback. [177] As can be seen in Figure 10b, the 3 dB linewidth of the high-order-mode Brillouin random fiber lasing (the red curve in the inset) is as narrow as 230 Hz, even with the pump linewidth of 15.2 kHz (the purple curve in Figure 10b). In such a BRFL, the FMF-based LPFG enables the transverse mode conversion among a broad wavelength range.…”
Section: Narrow-linewidth Rfls Based On Sbs Gain or Pmfmentioning
confidence: 91%
“…Among all gain mediums of RFLs, the SBS process has unique merits, such as low threshold and narrow gain bandwidth, which favors developing RFLs with narrow linewidth. [16,21,22,165,[174][175][176][177] Figure 10. Narrow-linewidth radiation of RFLs.…”
Section: Narrow-linewidth Rfls Based On Sbs Gain or Pmfmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al designed a Brillouin RFL based on a long-period fiber grating in a half-open linear cavity. Distributed RS was realized by SMF [11]. Rybaltovsky et al reported a ytterbium-doped RFL using FBG array, and discussed different cavity lengths in the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, RFLs have received a lot of attention due to their attractive features like low cost, simplicity of fabrication, and modeless lasing output. To date, RFLs based on a variety of gain mechanisms including rare-earth ion-doped fiber amplifiers, 16 stimulated Brillouin scattering (SBS), 17 stimulated Raman scattering, 18 , 19 and semiconductor optical amplifiers 20 have been reported. By employing regulating and control technologies combined with different gain mechanisms, performances of the reported RFLs have been well improved in many aspects, especially in their lower threshold, 21 higher output power, 22 wavelength tunability, 23 higher coherence, 24 narrower linewidth, 25 lower noise, 26 and more stabilized output power, 27 which enables a wide range of applications for RFLs in optical measurement, 28 microwave photonics, 29 optical fiber communication, 30 optical fiber sensing, 31 laser imaging, 32 and other fields 30 , 33 .…”
Section: Introductionmentioning
confidence: 99%